The Effect of Cultivation Techniques in The Dry and Rainy Seasons on The Quality of The Seaweed Caulerpa racemosa - Darmawati, Darmawati; Soedibya, Petrus Hary Tjahja; Anwar, Asni; Murni, Murni; Tang, Beddu (Journal of Aquaculture and Fish Health, 2024)
The seaweed Caulerpa racemosa has great potential to be developed because it has economic value and potential as a functional food. This seaweed contains nutrients, including protein, carbohydrates, polyunsaturated fatty acids, fiber minerals, and antioxidants. The availability of seaweed is still very dependent on nature and has not been appropriately cultivated. The planting season and appropriate cultivation methods will influence seaweed's quality/nutritional content. This research aims to analyze the nutritional content of seaweed C. racemosa cultivated in different growing seasons. The research method used a floating raft system with a completely randomized design and a factorial pattern carried out in two seasons, namely the dry and rainy seasons. Proximate analysis was carried out to determine the nutritional composition of seaweed C. racemosa, including protein, crude fiber, water, ash, fat, and carbohydrate (NFE). Next, it was analyzed using ANOVA with a further test with Tukey. The research results showed differences in the nutritional composition of seaweed C. racemosa from each treatment cultivated in the dry and rainy seasons. The nutritional composition of seaweed C. racemosa best treatment is found in the plant spacing of 30 cm with a depth of 50 cm in the dry season with the nutritional content namely protein (13.8%), NFE (20.75%), crude fiber (15.71%), a fluctuating fat content of 0.16-1.42%, highest ash (34.69%), water content (35%), moderate in the rainy season namely: protein (10.8%), BETN (10.78%), crude fiber (12.33%), fat content fluctuates (0.18-1.06%), highest ash (30.21%), water content (41.01%).